Time scales of autonomic information flow in near-term fetal sheep - Frasch, Martin; Frank, Birgit; Last, Michael; Mueller, Thomas (Frontiers in Physiology, 2012)
Autonomic information flow (AIF) characterizes fetal heart rate (FHR) variability (fHRV) in the time scale dependent complexity domain and discriminates sleep states (high voltage/low frequency (HV/LF) and low voltage/high frequency (LV/HF) electrocortical activity). However, the physiologic relationship of AIF time scales to the underlying sympathetic and vagal rhythms is not known. Understanding this relationship will enhance the benefits derived from using fHRV to monitor fetal health non-invasively. We analyzed AIF measured as Kullback-Leibler entropy in fetal sheep in late gestation as function of vagal and sympathetic modulation of fHRV, using atropine and propranolol respectively (n=6), and also analyzed changes in fHRV during sleep states (n=12). Atropine blockade resulted in complexity decrease at 2.5 Hz compared to baseline HV/LF and LV/HF states and at 1.6 Hz compared to LV/HF. Propranolol blockade resulted in complexity increase in the 0.8-1 Hz range compared to LV/HF and in no changes when compared to HV/LF. During LV/HF state activity, fHRV complexity was lower at 2.5 Hz and higher at 0.15-0.19 Hz than during HV/LF. Our findings show that in mature fetuses near term vagal activity contributes to fHRV complexity on a wider range of time scales than sympathetic activity. Related to sleep, during LV/HF we found lower complexity at short-term time scale where complexity is also decreased due to vagal blockade. We conclude that vagal and sympathetic modulations of fHRV show sleep state-dependent and time scale-dependent complexity patterns captured by AIF analysis of fHRV. Specifically, we observed a vagally mediated and sleep state-dependent change in these patterns at a time scale around 2.5 Hz (0.2 seconds). A paradigm of state-dependent nonlinear sympathovagal modulation of fHRV is discussed.